Pengaruh Pendidikan Dan Pengetahuan Terhadap Tingkat Pemahaman Masyarakat Kota Sibolga Dalam Memilih Produk Bank Syariah - Lubis, Melisa; Tambunan, Khairina (Jurnal Manajemen Akuntansi (JUMSI), 2024)
In Sibolga City, this study intends to examine public awareness of sharia banking products. A quantitative technique is used in this kind of research. Up to 100 residents of Sibolga City made up the sample for this study. By completing a questionnaire on a Likert scale, data was gathered. The study's findings support the conclusion that most residents of Sibolga City are unaware of Islamic banking products, with the exception of those who know about Islamic banks. The community in Sibolga City only knows about Islamic banks, according to the study's findings.